Evaluation of the Diagnostic Accuracy of Conventional 2‐Dimensional and 3‐Dimensional Computed Tomography for Assessing Canine Sacral and Pelvic Fractures by Radiologists, Orthopedic Surgeons, and Veterinary Medical Students. Issue 6 (22nd December 2014) - Stieger‐Vanegas, Susanne M.; Senthirajah, Sri Kumar Jamie; Nemanic, Sarah; Baltzer, Wendy; Warnock, Jennifer; Hollars, Katelyn; Lee, Scott S.; Bobe, Gerd
Abstract : Objective: To determine, using 3 groups of evaluators of varying experience reading orthopedic CT studies, if 3‐dimensional computed tomography (3D‐CT) provides a more accurate and time efficient method for diagnosis of canine sacral and pelvic fractures, and displacements of the sacroiliac and coxofemoral joints compared with 2‐dimensional computed tomography (2D‐CT). Study design: Retrospective clinical and prospective study. Animals: Dogs (n = 23): 12 dogs with traumatic pelvic fractures, 11 canine cadavers with pelvic trauma induced by a lateral impactor. Methods: All dogs had a 2D‐CT exam of the pelvis and subsequent 3D‐CT reconstructions from the 2D‐CT images. Both 2D‐CT and 3D‐CT studies were anonymized and randomly presented to 2 veterinary radiologists, 2 veterinary orthopedic surgeons, and 2 veterinary medical students. Evaluators classified fractures using a confidence scale and recorded the duration of evaluation for each modality and case. Results: 3D‐CT was a more time‐efficient technique for evaluation of traumatic sacral and pelvic injuries compared with 2D‐CT in all evaluator groups irrespective of experience level reading orthopedic CT studies. However, for radiologists and surgeons, 2D‐CT was the more accurate technique for evaluating sacral and pelvic fractures. Conclusion: 3D‐CT improves sacral and pelvic fracture diagnosis when added to 2D‐CT; however, 3D‐CT has a reduced accuracy for evaluation of sacral and pelvic fractures if used without concurrent evaluation of 2D‐CT images.